KARRÂMÎ NAMES THAT HAD BEEN EFFECTIVE IN NISHABUR - Alimoglu, Zeynep Surmeli (Kyrgyz-Turkish Manas University, 2017)
Karrâmiyya, about which there are insufficient studies in Islamic intellectual history, appears at the end of h. III. century and gains a lot of followers in Horasan and Transoxiana regions. The first Karrâmiyya, which we limited with the period until early fourth century after the hegira, has shown a sufi structuring rather than a theological school and most probably because of this property, it was not considered as a separate sect and has been considered within the Murci’ah. The pioneering Karrâmî scholars’ascetic lifestyles have been influential upon this situation. After İbn Kerrâm, with contributions of important Karrami names like Mohammad b. Haysam,Karrâmiyya has turned into a sect which has a specific theology. The activities of nearly all of the people who were influential in this conversion were focused on Nishabur, and because of this, Karrami names who have come to the fore in Nishabur and their affects in the organization of the Karrâmiyya have been emphasized in this study

Hakkında pek az çalışma bulunan Kerrâmiyye, hicri üçüncü asrın sonlarından itibaren tarih sahnesine çıkar ve Horasan-Maveraünnehir bölgelerinde pek çok taraftar edinir. Hicri dördüncü asrın başlarına kadar olan zaman dilimi ile sınırlandırmış olduğumuz ilk dönem Kerrâmiliği, kelami bir mezhepten ziyade sufi bir yapılanma arz etmiş ve bu özelliğinden olsa gerek müstakil bir fırka muamelesine tabi tutulmaksızın çoğunlukla Mürcie içerisinde değerlendirilmiştir. Önde gelen Kerrâmi şahsiyetlerin zâhidâne yaşayışları bunda etkili olmuştur. İbn Kerrâm’dan sonraMuhammed b. Heysem gibi önemli isimlerin katkısı ile Kerrâmilik, kendine has teolojisi olan bir mezhebe dönüşmüştür. Mezhebin söz konusu dönüşümünde etkili olan şahsiyetlerin tamamına yakını ise faaliyetlerini Nişabur’da yoğunlaştırmıştır. Bundan dolayı bu makalede Nişabur’da ön plana çıkmış Kerrâmi şahıslar ve bu şahısların Kerrâmiyye’nin teşekkülündeki etkileri üzerinde durulmuştur
Nisabur’da Etkili Olmuş Kerâmî Şahsiyetler